The organization of spinal motor neurons in a monotreme is consistent with a six-region schema of the mammalian spinal cord - Mitchelle, A.; Watson, Charles (Wiley Blackwell Publishing Ltd, 2016)
The motor neurons in the spinal cord of an echidna (Tachyglossus aculeatus) have been mapped in Nissl-stained sections from spinal cord segments defined by spinal nerve anatomy. A medial motor column of motor neurons is found at all spinal cord levels, and a hypaxial column is found at most levels. The organization of the motor neuron clusters in the lateral motor column of the brachial (C5 to T3) and crural (L2 to S3) limb enlargements is very similar to the pattern previously revealed by retrograde tracing in placental mammals, and the motor neuron clusters have been tentatively identified according to the muscle groups they are likely to supply. The region separating the two limb enlargements (T4 to L1) contains preganglionic motor neurons that appear to represent the spinal sympathetic outflow. Immediately caudal to the crural limb enlargement is a short column of preganglionic motor neurons (S3 to S4), which it is believed represents the pelvic parasympathetic outflow. The rostral and caudal ends of the spinal cord contain neither a lateral motor column nor a preganglionic column. Branchial motor neurons (which are believed to supply the sternomastoid and trapezius muscles) are present at the lateral margin of the ventral horn in rostral cervical segments (C2–C4). These same segments contain the phrenic nucleus, which belongs to the hypaxial column. The presence or absence of the main spinal motor neuron columns in the different regions echidna spinal cord (and also in that of other amniote vertebrates) provides a basis for dividing the spinal cord into six main regions – prebrachial, brachial, postbrachial, crural, postcrural and caudal. The considerable biological and functional significance of this subdivision pattern is supported by recent studies on spinal cord hox gene expression in chicks and mice. On the other hand, the familiar ‘segments’ of the spinal cord are defined only by the anatomy of adjacent vertebrae, and are not demarcated by intrinsic gene expression. The recognition of segments defined by vertebrae (somites) is obviously of great value in defining topography, but the emphasis on such segments obscures the underlying evolutionary reality of a spinal cord comprised of six genetically defined regions. The six-region system can be usefully applied to the spinal cord of any amniote (and probably most anurans), independent of the number of vertebral segments in each part of the spinal column.